2021
DOI: 10.1101/2021.03.18.435986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploration-based learning of a step to step controller predicts locomotor adaptation

Abstract: Humans are able to adapt their locomotion to a variety of novel circumstances, for instance, walking on diverse terrain and walking with new footwear. During locomotor adaptation, humans have been shown to exhibit stereotypical changes in their movement patterns. Here, we provide a theoretical account of such locomotor adaptation, positing that the nervous system prioritizes stability in the short timescale and improves energy expenditure over a longer timescale. The resulting mathematical model has two proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 62 publications
1
14
2
Order By: Relevance
“…This evolution of step length asymmetry is associated with a decrease in energy cost between early and late adaptation, consistent with the theory that people are adapting to take advantage of positive work performed by the treadmill. This trend toward positive asymmetry during split-belt adaptation has also been observed in previous work modeling split-belt walking with bipedal robots (Fujiki et al, 2015; Otoda et al, 2009; Simha, 2020; Seethapathi et al, 2021).…”
Section: Simulation Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This evolution of step length asymmetry is associated with a decrease in energy cost between early and late adaptation, consistent with the theory that people are adapting to take advantage of positive work performed by the treadmill. This trend toward positive asymmetry during split-belt adaptation has also been observed in previous work modeling split-belt walking with bipedal robots (Fujiki et al, 2015; Otoda et al, 2009; Simha, 2020; Seethapathi et al, 2021).…”
Section: Simulation Results and Discussionsupporting
confidence: 86%
“…Our work adds to the body of literature using simulation models to understand human split-belt walking. Previous work has shown that bipedal robots on split-belt treadmills adapt from negative asymmetry toward positive asymmetry (Fujiki et al, 2015; Otoda et al, 2009; Simha, 2020; Seethapathi et al, 2021); our paper helps explain why this adaptation could be beneficial in allowing the treadmill to do work on the person. More complicated simulation models, as well as future human-subject experiments, can further reveal the opportunities and limitations for humans to take advantage of the split-belt treadmill.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…While these two modeling approaches are useful, there still exists a need for a robust model which can simulate longterm adaptations to persistent foot-ground contact asymmetry. Methods such as single-shooting optimal control [26], [27] and reinforcement learning [28], [29] are better suited for simulating interactive perturbations and observing the change in behavior and may be appropriate for modeling the immediate aftermath of large stiffness or damping perturbations. There is also a need for new experiments using a VST to perform prolonged perturbations with additional EMG and kinematic data for both lower limbs, and to perform long term adaptation studies in general.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation of SLA during split-belt walking occurs at two distinct rates -a fast component that adapts rapidly and a slow component that adapts more gradually (Darmohray et al, 2019;Mawase et al, 2013;Roemmich et al, 2016;Sánchez et al, 2021). Recently, Seethapathi and colleagues computationally posited that the fast component that adapts rapidly is driven by balance optimization, whereas the slow component that adapts more gradually is driven by energetic cost optimization (Seethapathi et al, 2021). SLA adaptation during split-belt walking occurs in parallel with reductions in the work generated by the legs; gait adaptation results in decreasing positive work and increasing negative work done by the legs, especially the leg on the fast belt (Sánchez et al, 2019;Selgrade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%